The growth of US credit unions - Goddard, John A; McKillop, Donal G; Wilson, John O.S (Journal of Banking & Finance, 2002)
The growth of US credit unions during the 1990s is investigated empirically, using univariate and multivariate cross sectional and panel estimation techniques. Univariate tests of the law of proportionate effect suggest that in general large credit unions grew faster than their smaller counterparts. On average credit unions with above-average growth in one period tended to experience below-average growth in the next. Smaller credit unions tended to have more variable growth than large ones. While credit unions share a common co-operative philosophy, they differ in terms of age profile, scope for membership growth, charter type and financial structure and performance. In estimations of a multivariate growth model, most of these characteristics are found to have a significant influence on the size-growth relationship. While large state chartered credit unions grew faster than their smaller counterparts, the reverse was true for federally chartered credit unions. In general, if larger credit unions grew faster than smaller ones, they tended to do so for specific reasons: because their charters were less restrictive, because they were more efficient, or because they had a financial structure that was more conducive to growth. Therefore credit union growth was not `random', but highly systematic.